PENGARUH STRUKTUR KEPEMILIKAN DAN DEWAN KOMISARIS TERHADAP KINERJA BANK UMUM KONVENSIONAL YANG MENYALURKAN KREDIT PADA UMKM: DENGAN KESEMPATAN INVESTASI SEBAGAI VARIABEL MEDIASI - Sri Ayem (Jurnal Akuntansi, 2016)
There were two aims of the research. The first one was to test the influence of corporate governance structures: institution ownership, public ownership, and board of director structure--toward the corporate performance, and the second aim was to test the possibility of investment opportunity set variable (IOS) play the role as a mediated variable between corporate governance structure and corporate performance. Previous researches done on the same topic had dominantly focused on direct relationship of corporate governance and corporate performance. So far, the results of those researches were not conclusive yet. The banking corporations used as the sample were taken from the Indonesian Stock Exchange (Jakarta Stock Exchange) which were active during the period of 2005-2011. Among 27 corporations, there were only 20 that fulfilled the sample requirements. The data were collecting by using pooling method ( data panel ) within 147 investigations. The test results substructure one that examines the effect of institutional ownership, public ownership and composition of the board of directors of the investment opportunity set, showing the ownership structure (institutional ownership and public) did not significantly influence the investment opportunity, while the composition of the board of commissioners statistically have an influence on the investment opportunity set , Based on testing substructure 2 which tested the effect of the structure of institutional ownership, structure of public ownership, the board and the investment opportunity set on firm performance indicate ownership variables Institutional has no significant effect on the performance of commercial banks Conventional loan portfolio on SMEs, while public ownership, the composition of the board of commissioners and the investment opportunity set has a significant influence on the company's performance. Keyword: corporate governance structures, management ownership, Institutional ownership, board of director, investment opportunity set, corporate performances